2017
DOI: 10.1021/acs.iecr.7b02329
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Oxidation and Its Removal in Mist by Nonthermal Plasma: Effects of Discharge Conditions

Abstract: A coaxial nonthermal plasma (NTP) reactor was used for the removal of nitric oxide in mist. The effects of discharge gap, thorn number, tooth slice number as well as discharge polarity on NO oxidation and NO x removal were investigated. Decreasing the discharge gap is favorable for the NO oxidation and NO x removal. The mist is almost captured completely even under a relative low input energy. Increasing the thorn number of discharge slice or tooth slice number facilitates the energy input in the plasma reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…To reduce air pollution resulted from NO x , advances in NO x removal technology have drawn much attention and been quite rapid. NO oxidation plays an increasingly significant role in NO x removal technologies (Bray and Schneider, 2015;Xie et al, 2017), including NO x storage and reduction (Lin et al, 2013;Zhang et al, 2016), selective catalytic reduction (Zahaf et al, 2015;Guo et al, 2017), dry sorbent injection (Rezaei et al, 2015) and absorption in wet flue gas desulfurization (Liu et al, 2014;Guo et al, 2015b). Cerium oxide has been widely utilized in catalysts pleased in these mobile source and stationary source applications, due to its outstanding oxygen storage capacity (OSC) (Atribak et al, 2008;Zhang et al, 2011;Hong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To reduce air pollution resulted from NO x , advances in NO x removal technology have drawn much attention and been quite rapid. NO oxidation plays an increasingly significant role in NO x removal technologies (Bray and Schneider, 2015;Xie et al, 2017), including NO x storage and reduction (Lin et al, 2013;Zhang et al, 2016), selective catalytic reduction (Zahaf et al, 2015;Guo et al, 2017), dry sorbent injection (Rezaei et al, 2015) and absorption in wet flue gas desulfurization (Liu et al, 2014;Guo et al, 2015b). Cerium oxide has been widely utilized in catalysts pleased in these mobile source and stationary source applications, due to its outstanding oxygen storage capacity (OSC) (Atribak et al, 2008;Zhang et al, 2011;Hong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the benzene oxidation rate decreases with an increase of the Si/Al ratio from 2.6 to 40, while the discharge region was also significantly reduced, as obtained by ICCD camera. Xie et al compared the effect of Al 2 O 3 , L-MgO and H-MgO on NH 3 yield in a dielectric barrier discharge (DBD) reactor [17]. The results showed that the presence of H-MgO could slightly improve the NH 3 yield by 4% to 9.5% in the temperature range between 140 • C to 260 • C. To the best of our knowledge, most previous work mainly focused on the effect of support composition on the performance of soot oxidation, the mechanisms of how the physical structure of the support would affect the plasma-catalytic system, especially in the process of soot oxidation, were far from clearly understood [18,19].…”
Section: Introductionmentioning
confidence: 99%